Evaluating the utility of B/Ca ratios in planktic foraminifera as a proxy for the carbonate system: A case study of Globigerinoides ruber. (4th April 2015) - Henehan, Michael J.; Foster, Gavin L.; Rae, James W. B.; Prentice, Katy C.; Erez, Jonathan; Bostock, Helen C.; Marshall, Brittney J.; Wilson, Paul A.
Abstract B/Ca ratios in foraminifera have attracted considerable scientific attention as a proxy for past ocean carbonate system. However, the carbonate system controls on B/Ca ratios are not straightforward, with Δ[ <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjnf8pmmc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO32−</alternatives>] ([ <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjnf8pmnw" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO32−</alternatives>]in situ – [ <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjnf8pmjb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CO32−</alternatives>]at saturation) correlating best with B/Ca ratios in benthic foraminifera, rather than pH, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjnf8pmkv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B(OH)4−HCO3−</alternatives>, or <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjnf8pmg9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B(OH)4−DIC</alternatives> (as a simple model of boron speciation in seawater and incorporation into CaCO3 would predict). Furthermore, culture experiments have shown that in planktic foraminifera properties such as salinity and [B]sw can have profound effects on B/Ca ratios beyond those predicted by simple partition coefficients. Here, we investigate the controls on B/Ca ratios in G. ruber via a combination of culture experiments and core‐top measurements, and add to a growing body of evidence that suggests B/Ca ratios in symbiont‐bearing foraminiferal carbonate are not a straightforward proxy for past seawater carbonate system conditions. We find that while B/Ca ratios in culture experiments covary with pH, in open ocean sediments this relationship is not seen. In fact, our B/Ca data correlate best with [ <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjnf8pmht" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO43−</alternatives>] (a previously undocumented association) and in most regions, salinity. These findings might suggest a precipitation rate or crystallographic control on boron incorporation into foraminiferal calcite. Regardless, our results underscore the need for caution when attempting to interpret B/Ca records in terms of the ocean carbonate system, at the very least in the case of mixed‐layer planktic foraminifera.